Sexual Dimorphism of the First Rib: A Comparative Approach Using Metric and Geometric Morphometric Analyses1. Issue 5 (7th February 2017) - Lynch, Jeffrey James; Cross, Peter; Heaton, Vivienne
Abstract: This research investigated the sexual dimorphism of the first human rib using geometric morphometric and metric approaches on a sample of 285 specimens containing European Americans and African Americans from the Hamann‐Todd collection. Metric measurements were investigated for sexual dimorphism and ancestral differences using univariate statistics. Four type II landmarks and 40 sliding semi‐landmarks were placed outlining the dorsal and ventral curvatures of the ribs. Landmark data were processed using Generalized Procrustes Analyses with Procrustes distance sliding, and the subsequent coordinates were investigated for sexual dimorphism and ancestral differences using Procrustes ANOVAs. Both geometric morphometric and metric data were analyzed using cross‐validated discriminant function analyses to test the hypothesis that variables from both approaches can be combined to increase sex classification rate. European Americans had sex correctly classified as high as 88.05% and African Americans as high as 70.86% using a combination of metric and geometric morphometric variables.